Transient conjugate free convection from a vertical flat plate in a porous medium subjected to a sudden change in surface heat flux - Shu, Jian Jun (2011)
The paper presents a theoretical study using Kármán–Pohlhausen method for describing the transient heat exchange between the boundary-layer free convection and a vertical flat plate embedded in a porous medium. The unsteady behaviour is developed after generation of an impulsive heat flux step at the right-hand side of the plate. Two cases are considered according to whether the plate has a finite thickness or has no thickness. The time and space evolution of the interface temperature is evidenced.